2018
DOI: 10.1074/jbc.m117.813741
|View full text |Cite
|
Sign up to set email alerts
|

Aspartyl proteases in Candida glabrata are required for suppression of the host innate immune response

Abstract: A family of 11 cell surface-associated aspartyl proteases (CgYps1–11), also referred as yapsins, is a key virulence factor in the pathogenic yeast Candida glabrata. However, the mechanism by which CgYapsins modulate immune response and facilitate survival in the mammalian host remains to be identified. Here, using RNA-Seq analysis, we report that genes involved in cell wall metabolism are differentially regulated in the Cgyps1–11Δ mutant. Consistently, the mutant contained lower β-glucan and mannan levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(88 citation statements)
references
References 55 publications
4
84
0
Order By: Relevance
“…The ability of C. glabrata to form biofilms has also been found to be enhanced in the high-iron environment [57]. Moreover, recent studies have shown a close association between the capacity to form biofilms and colonize murine organs in the systemic candidiasis model [57,58], however, the precise mechanisms underlying this relationship are unknown.…”
Section: Salient Pathobiological Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability of C. glabrata to form biofilms has also been found to be enhanced in the high-iron environment [57]. Moreover, recent studies have shown a close association between the capacity to form biofilms and colonize murine organs in the systemic candidiasis model [57,58], however, the precise mechanisms underlying this relationship are unknown.…”
Section: Salient Pathobiological Featuresmentioning
confidence: 99%
“…CgYPS genes have been shown to be regulated by various environmental conditions including low pH, thermal stress, macrophage and neutrophil internalization [60,61,62,63]. Consistently, CgYapsins are pivotal to the regulation of several cellular processes such as maintenance of the cell wall architecture, pH and vacuole homeostasis, biofilm formation and interaction with the host [58,60,61,64]. The latter includes suppression of the production of pro-inflammatory cytokine IL-1β in human THP-1 macrophages, facilitating survival in macrophages and virulence in the models of murine systemic candidiasis and Drosophila melanogaster [58,60,65,66].…”
Section: Salient Pathobiological Featuresmentioning
confidence: 99%
See 3 more Smart Citations